0181 Stressor Reactivity to Insufficient Sleep in Oncology Nurses: Does Work Shift Matter?. (27th May 2020) - Vigoureux, T F; Lee, S
Abstract: Introduction: Individuals generally perceive more stressors on days following nights with shorter-than-usual sleep duration. Recent research shows that this daily sleep—stress relationship (i.e., stressor reactivity to insufficient sleep) is stronger for some than for others. Workers in certain occupations, such as oncology nurses, may be more prone to insufficient sleep and/or more stressors. Given the impact of work schedule on sleep, this study examined whether stressor reactivity to insufficient sleep differed between day and night shift nurses working at a cancer hospital. Methods: Participants were 39 day-shift and 19 night-shift nurses at a cancer hospital (Mage =35.36±12.00). Using ecological momentary assessments for 14 days, we asked participants about their previous night's sleep characteristics and their daily stressor frequency and severity before lunch, during afternoon, and before bedtime. Using multi-level modeling, we tested whether previous night's sleep duration, quality, or sufficiency predicted next day's total stressor frequency or severity. For analyses with significant within-person effects, we extracted a reactivity slope for each participant. We used t-tests to examine whether day and night shift nurses differed in reactivity. Results: There were significant within-person associations of sleep duration with (a) stressor frequency (b=-.07, p<.001) and (b) stressor severity (b=-.76, p<.001), but no associations of sleep quality or sufficiency with stressor frequency or severity. Day and night shift nurses did not differ in either of these operationalizations of stressor reactivity to insufficient sleep, or on any stressor or sleep variables except for average sleep duration (Mnight =6.87±2.57 vs. Mday =8.02±1.84, p<.001). Conclusion: These findings suggest that the phenomenon of perceiving more stressors in response to insufficient sleep exists regardless of work shifts. Given the previously found association between stressor reactivity to insufficient sleep and body mass index in middle-aged workers, further analyses will test how this reactivity is associated with health outcomes in oncology nurses. Support: This work was supported, in part, by the University of South Florida College of Behavioral & Community Sciences Internal Grant Program (PI: Lee, Grant No. 0134930).